1985
DOI: 10.1128/iai.47.2.489-495.1985
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase from Streptococcus mutans: purification, characterization, and crossed antigenicity with lactate dehydrogenases from Lactobacillus casei, Actinomyces viscosus, and Streptococcus sanguis

Abstract: A cytoplasmic fructose-1,6-diphosphate-dependent lactate dehydrogenase (LDH; EC 1.1.1.27) from Streptococcus mutans OMZ175 was purified to homogeneity as judged by sodium dodecyl sulfate-gel electrophoresis. The purification consisted of ammonium sulfate precipitation of the cytoplasmic fraction, DEAE-Sephacel and Blue-Sepharose CL.6B chromatography, and Sephacryl S200 gel permeation. The catalytic activity of the purified enzyme required the presence of fructose-1,6-diphosphate with a broad optimum between pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…A significant degree of similarity exists between their active centers, at least for the Lactobacillus casei (14) and the Streptococcus cremoris (7) enzymes, when respectively compared with vertebrate enzymes. Immunological crossreactions between extragenera lactic bacterial LDHs revealed antigenic relationships (21), confirming the structural conservation of these molecules.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…A significant degree of similarity exists between their active centers, at least for the Lactobacillus casei (14) and the Streptococcus cremoris (7) enzymes, when respectively compared with vertebrate enzymes. Immunological crossreactions between extragenera lactic bacterial LDHs revealed antigenic relationships (21), confirming the structural conservation of these molecules.…”
supporting
confidence: 54%
“…Organisms, culture conditions, and enzyme purification. S. mutans OMZ 175 (serotype f, 3, 19), S. sanguis OMZ 9, A. viscosus NY.1, and L. casei ATCC 4646 were previously described (20,21). Bacteria were prepared from exponentialphase cultures grown in brain heart infusion broth (Difco Laboratories, Detroit, Mich.).…”
Section: Methodsmentioning
confidence: 99%
“…1). In this case, inhibition of LDH would most likely occur due to decreases in the levels of glycolytic intermediates and, in particular, fructose-1,6-bis-phosphate, which is an allosteric activator of LDH (30).…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis is another important sucrose metabolism pathway in S. mutans. In this process, LDH catalyzes the conversion of pyruvate to lactic acid, which in turn reduces the pH of the environmental medium (34). Our results showed that the unit bacterial count activity of LDH was markedly increased at an oxyresveratrol concentration of 62.5 lg ml À1 and showed smaller increases at 125 and 250 lg ml À1 of oxyresveratrol: however, all were still significantly higher than the unit bacterial count activity of LDH in the control group.…”
Section: Discussionmentioning
confidence: 57%